Enterocytozoon bieneusi Identification Using Real-Time Polymerase Chain Reaction and Restriction Fragment Length Polymorphism in HIV-Infected Humans from Kinshasa Province of the Democratic Republic of Congo - Roger Wumba; Menotti Jean; Longo-Mbenza Benjamin; Mandina Madone; Kintoki Fabien; Zanga Josué; Sala Jean; Kendjo Eric; Guillo-Olczyk AC; Thellier Marc (Journal of Parasitology Research)
Objective. To determine the prevalence and the genotypes of Enterocytozoon bieneusi in stool specimens from HIV patients. Methods. This cross-sectional study was carried out in Kinshasa hospitals between 2009 and 2012. Detection of microsporidia including E. bieneusi and E. intestinalis was performed in 242 HIV-infected patients. Typing was based on DNA polymorphism of the ribosomal DNA ITS region of E. bieneusi. PCRRFLP generated with two restriction enzymes (Nla III and Fnu 4HI) in PCR-amplified ITS products for classifying strains into different lineages. The diagnosis performance of the indirect immune-fluorescence-monoclonal antibody (IFI-AcM) was defined in comparison with real-time PCR as the gold standard. Results. Out of 242 HIV-infected patients, using the real-time PCR, the prevalence of E. bieneusi was 7.9% (n=19) among the 19 E. bieneusi, one was coinfected with E. intestinalis. In 19 E. bieneusi persons using PCR-RFLP method, 5 type I strains of E. bieneusi (26.3%) and 5 type IV strains of E. bieneusi (26.3%) were identified. The sensitivity of IFI-AcM was poor as estimated 42.1%. Conclusion. Despite different PCR methods, there is possible association between HIVinfection, geographic location (France, Cameroun, Democratic Republic of Congo), and the concurrence of type I and type IV strains.